Implementasi Kebijakan Program Safety Riding Dalam Meningkatkan Keselamatan Berkendara Di Satuan Lalu Lintas Polres Mojokerto Kota - Santoso, Heru Sudjio Budi; Priyanto (Soetomo Magister Ilmu Administrasi, 2023)
Traffic discipline behavior is behavior that is influenced by the age level with increasing age of a person whose behavior is expected to be more directed because they have good emotional intelligence and are not easily emotional, so they can comply with applicable regulationsin driving. Safety riding or driving safety is an effort which aims to minimize the level of danger so as to maximize driving safety, create conditions that will not endanger other motorists, and understand prevention and handling. Safety riding is a guide for driving behavior in order to minimize risk and maximize safety when driving in every mode of transportation. Writing this research using a type of qualitative descriptive research. A qualitative approach is a research process based on a methodology that investigates a social phenomenon. In this approach, the researcher is the key instrument and the researcher must have a very broad theory and insight in order to be able to dig up information, ask questions, and analyze the object to be studied more clearly. Qualitative research is used if the problem to be studied is still unclear, and also to develop theory, and to ensure the correctness of the data. In the success of the safety riding program, the Mojokerto City Police Traffic Unit conducts socialization to various elements of society, both the general public, motorcycle communities and other communities as well as students about how to drive properly, correctly and safely by organizing safety riding socialization activities. Then there is the safety riding training which is carried out by inviting the general public to learn more about how to drive properly and safely. The people of Mojokerto Kota and its surroundings have access to safety riding training free of charge. This safety riding training more or less provides many benefits of Safety Riding Training. Keywords: Policy Implementation, Safety Riding Exercise